How Consumers use Gift Certificates - Flora Felso; Adriaan R. Soetevent (Tinbergen Institute, 2012)
There are two important reasons for consumers to spend gift certificates differently than gifts in cash or non-gift income: a) they are forced to change their shopping pattern because of the conditions imposed by the issuer of the certificates, or b) they purposely separate gift certificates from other sources of income. The first reason implies a welfare loss, the second reason does not. We survey consumers who have just redeemed one or more gift certificates. For the gift certificate considered in our empirical application, we find that consumers are not constrained by the set of accepting merchants but that they do make some small changes in the timing of expenditures because of the certificate's no-refund policy. About 14 percent of recipients separate their gift certificates from other income sources in order to buy a product they really love to have. Males tend to spend the certificates on ordinary items, whereas females are more likely to treat themselves by buying more personalized items.
Keywords: D11; D12; D31; 330; gift giving; labeling